Differentiation of Blastocystis Subtypes and Their Association with Gut Microbiota in Type 2 Diabetes Mellitus Patients And Non-Diabetic Individuals - Nurul Saadah binti Mohd Shaari (Universiti Sains Islam Malaysia, 2024)
Matric: 3192587 (FPSK)